Predictors of pregnant women's intention to vaccinate against coronavirus disease 2019: A facility-based cross-sectional study in southwest Ethiopia. (August 2021) - Hailemariam, Shewangizaw; Mekonnen, Besufekad; Shifera, Nigusie; Endalkachew, Biruk; Asnake, Molla; Assefa, Ashenafi; Qanche, Qaro
Objective: Ethiopia is planning to vaccinate 20% of its population against the coronavirus disease 2019 pandemic by the end of 2021—however, there is no single piece of evidence regarding pregnant women's intention to be vaccinated against coronavirus disease 2019; hence, the objective of this study was to investigate predicting factors of intention to be vaccinated against coronavirus disease 2019 among pregnant women in Bench-Sheko Zone, southwest Ethiopia. Methods: Facility-based cross-sectional study was undertaken from 1 February to 1 March 2021 in southwest Ethiopia. The study was carried out among pregnant women who came for antenatal care service in the selected public health facilities. Interviewer-administered structured tool was used to collect the data. Data were entered into EpiData (version 3.1) and then analyzed using SPSS (version 20). Results: The study revealed that only 31.3% (95% confidence interval: 26.7–35.2) of the participants had an intention to be vaccinated against coronavirus disease 2019 when the vaccine will be made available in Ethiopia. Participants' intention to be vaccinated against coronavirus disease 2019 was significantly associated with attaining secondary school and above (adjusted odds ratio = 4.24, 95% confidence interval: 2.23–9.32), residing in urban areas (adjusted odds ratio = 2.57, 95% confidence interval: 1.22–5.40), being compliant with coronavirus disease 2019 guidelines (adjusted odds ratio = 5.86, 95% confidence interval: 3.40–10.09), and having good perception toward coronavirus disease 2019 vaccine (adjusted odds ratio = 3.04, 95% confidence interval: 1.64–5.62). Conclusion: Above all, in this study, pregnant women's intention to vaccinate against coronavirus disease 2019 was very low when compared with previous studies. Hence, before commencing the coronavirus disease 2019 vaccination program in Ethiopia, it is essential to launch a widespread public health education campaign that could improve people's perception of the vaccine. Besides, the upcoming public health intervention programs better put special emphasis on community members with lower educational attainment backgrounds and rural residents.